Physical preparedness and functional status of young players in the competition period - Svystun, Yu.D.; Trach, V.M.; Chornobaj, I. M.; Shavel, Kh. E. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : evaluate physical preparedness and functional status of young players in the competitive period. Material : the study involved two groups of players. One group - 18 athletes aged 13 years. The second group - 16 players aged 14-16 years. Athletes performed tests: running 15 m stroke and 15 m, 30 m from the spot. Determines the amount of creatinine in the urine of athletes. Results : the evaluation of physical preparedness of young players indicates a decrease in the speed of the players, as evidenced by indicators and creatinine excretion in the urine. Revealed hypertrophy of the left ventricle, systolic blood volume. Functional state of the older age group athletes is somewhat better than the younger players. Analysis of the studied parameters indicates incomplete recovery of the body of young players. Conclusions : It is recommended to use the results to correct the training process of young players.